Business innovation through blockchain : the B3 perspective - Morabito, Vincenzo, ....- (S.l. : Springer International Publishing AG, 2017)
This book explores the main challenges and trends related to the use of blockchain technology for digital business innovation with the aim of providing practitioners with stimulating insights and ideas.
Keywords: Blockchain ; innovatie